HAK ASASI MANUSIA DI INDONESIA BERDASARRKAN UUD I945 - Nur Latifa Az-Zahara; Mulya Mulawarni; Arif Fadilah (Cahaya Ilmu Bangsa Institute, 2025)
The purpose of this journal is to find out about Human Rights in Indonesia based on the 1945 Constitution. Human rights (HAM) are basic rights that are inherently inherent in humans, are universal and eternal which must be protected, respected, maintained, and must not be ignored, reduced, or taken away by anyone, including the government and state apparatus. The state, through the 1945 Constitution and a number of legal instruments, has guaranteed the protection of human rights contained in various articles of the 1945 Constitution. Indonesia as a state of law must have Human Rights based on the 1945 Constitution which reflects respect for Human Rights. The method used is collecting, analyzing, and using relevant literature studies from various sources, be it from books, journals, articles, and other trusted sources.